The Effect of a Midwife-Based Group Discussion Education on Sexual Dysfunction Beliefs in Rural Postmenopausal Women - Sasanpour M; Azh N; Alipour M (Dove Medical Press, 2020)
Maryam Sasanpour,1 Nezal Azh,2 Mahmoud Alipour3 1Student Research Committee, Qazvin University of Medical Sciences, Qazvin, Iran; 2Faculty of Nursing and Midwifery, Qazvin University of Medical Sciences, Qazvin, Iran; 3Faculty of Medicine, Qazvin University of Medical Sciences, Qazvin, IranCorrespondence: Nezal AzhFaculty of Nursing and Midwifery, Qazvin University of Medical Sciences, Qazvin, IranEmail nezalazh20@gmail.comIntroduction: Correcting sexual beliefs can affect women’s sexual function. There are very limited interventional studies on correcting the sexual dysfunction beliefs in postmenopausal women living in rural areas. Therefore, the present study was carried out with the aim of investigating the effect of a midwife-based group education on sexual dysfunction beliefs in one group of rural postmenopausal women.Methods: The present study was a quasi-experimental pre–post design without a control group. The study population included rural menopausal women who referred to rural health centers. The study sample consisted of 50 participants who have all received education program. The education was held in six group discussion sessions. The data gathering tool used in this study was the Sexual Dysfunctional Beliefs Questionnaire which was completed before and after the education. This questionnaire consists of 33 items and includes 6 subscales.Results: The mean age of participants was 53.26 years. Approximately half of the participants (48%) had primary education. The mean scores of sexual dysfunction beliefs before and after education were 114.58 and 58.56, respectively (p-value< 0.001). The mean scores of sexual conersations, affection primacy, motherhood-related beliefs, sexual desire and pleasure as sin beliefs, age-related beliefs, and body image beliefs before intervention were 14.38, 21.38, 13.9, 23.64, 20.74, 17.04, respectively, and after intervention were 6.9, 11.80, 8.64, 12.48, 7.7, 9.40, respectively.Conclusion: Rural postmenopausal women had problems with sexual dysfunction beliefs. A midwife-based group discussion education on this matter had significantly improved the sexual dysfunction beliefs in them. Further studies are needed in this regard.Keywords: education, group discussion, menopause, rural women, sexual function, promoting sexual health